State of the planet the complete series - Attenborough, David (BBC Worldwide Ltd., 2005)
Deforestation, global warming, depletion of aquifers, rising sea levels, and mass extinctions--how much longer can Earth compensate for these damaging forces? In this timely three-part series, David Attenborough and some of the world's leading experts on environmental matters consider probably the most important issue of the 21st century: the future of life on this planet.